Influence Budaya Organisasi Dan Motivasi Terhadap Komitmen Organisasional Pegawai Inspektorat Daerah Kota Blitar - Eva Kartikasari; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2023)
The purposes of this research are: (a) To describe whether motivation has a positive and significant influence on the organizational commitment of the employees of the Regional Inspectorate of Blitar City; (b) To analyze whether organizational culture has a positive and significant influence on the organizational commitment of employees of the Regional Inspectorate of Blitar City; (c) To analyze whether organizational culture and motivation together have a positive and significant influence on the organizational commitment of the employees of the Regional Inspectorate of Blitar City; (d) To find out which variables of organizational culture and motivation have a dominant influence on organizational commitment of employees of the Regional Inspectorate of Blitar City. This study was conducted at the Regional Inspectorate of Blitar City with 34 employees as respondents. The method used in this study is a quantitative approach with a purpossive sampling mechanism as a data collection technique. The research data was obtained by using questionnaire, observation, and documentation techniques. The analysis technique used is multiple linear regression with F test and t test to test the research hypothesis. The results showed that, with the fulfillment of validity, reliability and classical assumption test, the hypothesis t test proved that organizational culture and motivation had a positive and significant effect on employee organizational commitment with an effective contribution of 66.90%. The F test hypothesis proves that together, the multiple regression model strengthens the correlational relationship between organizational culture and motivation to organizational commitment.